ANALISA PERFORMA DAN KONSUMSI BAHAN BAKAR PADA MESIN 4-TAK 113CC MENGGUNAKAN BAHAN BAKAR CAMPURAN PREMIUM DAN ETHANOL - Muhamad Hafidz Firdaus Priatama; Imron Rosyadi; Yusvardi Yusuf (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2020)
The use of a fuel mixture of gasoline and ethanol can reduce the PM2.5 (Particulate Matter) value in the air by 0.3-0.4 µg m-3. This research aims to see the performance of a 4-stroke engine 113cc in standard conditions using a mixture of premium and ethanol. This research learns 5 types of mixture, E0, E10, E15, E20, and E25. The fuels was tested at 5 engine speed 4000, 4500, 5000, 5500, and 6000 rpm, at prony brake dynamometer to measuring performance, fuel consumption and Specific Fuel Consumption (SFC). The results of research show that the highest torque and power is the E15 mixture, that is 8.90 Nm at 5500 rpm and the power obtained is 5.529 kW at 6000 rpm. Meanwhile, the lowest fuel consumption value is found in the E10 with a value of 169.78 gr/hour at 4500 rpm. The lowest SFC value of all fuels is the E15 at 5000 rpm on 27.565 gr/kW.h. This is the lowest of any other fuel, because the Research Octane Number value is following the compression ratio of the engine, so there is no delay in ignition symptoms that occur during the combustion system. The viscosity value also contributes to the difference in data.